(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
أجريت هذه التجربة في محطة بحوث حمضيات سيانو عام 2015 لدراسة الاستجابة الوظيفية والعددية للمفترس Aphidoletes aphidimyza عند تربيته على حوريات العمر الثالث لحشرة من القطن Aphis gossypii على أوراق نبات الخيار في الظروف المخبرية عند درجة حرارة 25 ± 2° C ورطوبة نسبية 70 %. أظهرت النتائج وجود علاقة ارتباط معنوية عالية جداً (r= 0.93) بين عدد الفرائس المستهلكة وكثافة الفريسة، فعند كثافة 5 فريسة استهلكت يرقة المفترس 2.8 ± 0.64 حورية / يوم، وازدادت هذه القيمة معنويا بشكل تدريجي عند زيادة كثافة الفريسة حتى وصلت إلى 34.2 ± 5.36 حورية / يوم عند كثافة 60 فريسة، و إلى 36.4 ± 5.72 حورية / يوم عند كثافة 80 فريسة. ولقد لوحظ أن ازدياد الاستجابة الوظيفية للمفترس مع زيادة كثافة الفريسة هذه تتوقف عند حد معين مما يشير إلى أن هذا المفترس يتبع النمط الثالث من الاستجابة الوظيفية حسب تقسيمات Holling (1959). أما فيما يخص الاستجابة العددية للمفترس، أدت زيادة كثافة الفريسة إلى زيادة معنوية في خصوبة الأنثى من 19 ± 4 بيضة / أنثى عند كثافة 5 فرائس إلى 28.6 ± 4.48 بيضة / أنثى عند كثافة 10 فرائس واستمرت هذه الزيادة حتى بلغت أعلى قيمة لها عند كثافة 80 فريسة ( 63.4 ± 6.48 بيضة / أنثى) . The functional and numerical response of Aphidoletes aphidimyza feeding on different densities of third instar nymphs of cotton aphid Aphisg ossypii on cucumber leaves was studied in laboratory at a temperature (25 ± 2 ° C) and relative humidity of 70 %. The predator consumed 2.8 ± 0.64 nymph/day, when prey density was 5 adults. The predator consumption increased with increasing prey density. At 60 and 80 preys the predator consumed 34.2 ± 5.36 and 36.4 ± 5.72 nymph /Day consequintly. Ther was a very high significant correlation (r = 0.93) between the number of prey consumed and the density of prey, So according Holling (1959) model of functional response, we put A. aphidimyza predator under the third type (type III). The increase of prey density caused increasing in egg numbers of predator The predator laid eggs in few numbers 19 ± 4.0 eggs / female when fed on 5 prey /day, and these numbers of eggs laid by predator increased to 28.6 ± 4.48 egg/female under prey density of 10 prey /day. the increase of eggs numbers reached to 63.4 ± 6.48 egg/female when prey density was 80 prey/day so we noticed the predator oviposition increased with high prey density, and these increase caused by increase in predation efficiency and these lead to another kind of response called numerical response.